Cross-cultural adaptation of the professional version of the Readiness for Interprofessional Learning Scale (RIPLS) in Japanese. Issue 1 (2nd January 2017) - Oishi, Ai; Haruta, Junji; Yoshimi, Kenji; Goto, Michiko; Yoshida, Kazue; Yoshimoto, Hisashi
ABSTRACT: Interprofessional education (IPE) for healthcare professionals is important in Japan because of its rapidly aging population and increasingly complex healthcare needs. However, no tools have been validated in the Japanese context to evaluate healthcare professionals' attitudes towards, or readiness for, IPE. The professional version of the Readiness for Interprofessional Learning Scale (RIPLS) with 23 items was selected for cross-cultural adaptation because it has been widely used internationally and a Japanese edition of the student version has already been developed. We followed a guideline for cross-cultural adaptation and subsequently conducted factor analysis with 368 responses from over 16 professions. Face and content validity was confirmed through the translation process. We obtained four factors with good internal consistency (Cronbach's alpha > 0.7). These results were similar to those of the original UK study, apart from one factor being divided into two different factors in this study. Studies are required to further confirm the rigor and generalisability of the results; however, the Japanese RIPLS can be used to evaluate healthcare professionals' attitudes towards IPE, which can eventually lead to a better IPE development for healthcare professionals in Japan.